Proton relays in anomalous carbocations dictate spectroscopy, stability, and mechanisms: case studies on C2H5+ and C3H3+. Issue 40 (9th October 2017) - Sager, LeeAnn M.; Iyengar, Srinivasan S.
Abstract : We present a detailed exposition of "Grothuss-like" proton shuttles in C2 H5 + and C3 H3 + that result in anomalous structural and spectral behavior. Abstract : We present a detailed analysis of the anomalous carbocations: C2 H5 + and C3 H3 + . This work involves (a) probing electronic structural properties, (b) ab initio dynamics simulations over a range of internal energies, (c) analysis of reduced dimensional potential surfaces directed along selected conformational transition pathways, (d) dynamically averaged vibrational spectra computed from ab initio dynamics trajectories, and (e) two-dimensional time–frequency analysis to probe conformational dynamics. Key findings are as follows: (i) as noted in our previous study on C2 H3 +, it appears that these non-classical carbocations are stabilized by delocalized nuclear frameworks and "proton shuttles". We analyze this nuclear delocalization and find critical parallels between conformational changes in C2 H3 +, C2 H5 +, and C3 H3 + . (ii) The vibrational signatures of C2 H5 + are dominated by the "bridge-proton" conformation, but also show critical contributions from the "classical" configuration, which is a transition state at almost all levels of theory. This result is further substantiated through two-dimensional time–frequency analysis and is at odds with earlier explanations of the experimental spectra, where frequencies close to the classical region were thought to arise from an impurity. While this is still possible, our results here indicate an additional (perhaps more likely) explanation that involves the "classical" isomer. (iii) Finally, in the case of C3 H3 + our explanation of the experimental result includes the presence of multiple, namely, "cyclic", "straight", and propargyl, configurations. Proton shuttles and nuclear delocalization, reminiscent of those seen in the case of C2 H3 +, were seen all through and have a critical role in all our observations.